THE MUSLIM EAST AND RADICALIZATION OF ISLAM IN THE NORTHERN CAUCASUS - MAGOMEDDADAEV, Amirkhan (CENTRAL ASIA AND THE CAUCASUS, 2005)
In the 1990s, extremist terrorist organizations and movements operating under religious and ethnic slogans and trying to impose their own ideological and moral principles on others became very active in the Northern Caucasus. Their radicalism and extremism stemmed from trends and organizations that tried, like ultra-left revolutionaries, to monopolize the right to speak for the people and express their interests and hopes. They distorted the Koran and the Sunna in an attempt to adjust them to their purely political aims. For this reason, it is hardly correct to use “Islamic terrorism” and the “Islamic threat” to describe extremist movements and groups acting in the Muslim world. All of them are out to change the social and political life of the Muslim countries according to the principles of “pure,” original Islam, which means that they are, in fact, apologists of the ideology known as Islamism. M. Roshchin, Ph.D. (Hist.), who is well known as an expert in Daghestan, has pointed out that the first seat of Islamic fundamentalism in the Northern Caucasus appeared in Daghestan, from where it gradually spread across the region. By the mid-1990s, the republic had already become the ideological center of fundamentalism, while Chechnia promptly developed into its proving ground. In 1989-1995, these structures were living on huge amounts of money from abroad, yet foreign influence was obvious even earlier. In the latter half of the 1980s, the founder and leader of the Islamic Jamaat Muhammad Bagauddin (Bagavudin Magomedovich Kebedov born, according to certain sources, in the Avar village of Santlada, Tsumadinskiy District of Daghestan, or in the Chechen village of Vedeno, according to other sources) “had contacts with embassies in several Arab countries, which supplied him with the literature he needed.”1 Foreign money helped build mosques and open teaching and propaganda centers in Makhachkala and Kiziliurt, foreigners paid for huge circulations of newspapers and magazines, and for the large number of copies of religious books. Numerous foreign delegations and individual functionaries visited the republic as missionaries and educators, wishing to learn more about the local situation. Arab and other Islamists used the visits to establish contacts with corresponding structures in Daghestan, to share experience with Muslim leaders, and to influence the ideological and political orientation of the local Muslims. “On 13 May 1989 a group of Islamists from Kirghizia, Turkmenia, Kazakhstan, and the North Caucasian republics held the so-called congress of Muslims in Buinaksk. The congress decided to capture the Spiritual Administration of the Muslims of the Northern Caucasus. Later, they were active in the villages of Agvali (the Tsumadinskiy District), Erpeli (the Buinaksk District), Kaiakent (the Kaiakent District), in villages of the Buinaksk andGunib districts, and in the city of Khasaviurt.